PARTISIPASI ORANG TUA PENGARUHNYA TERHADAP PRESTASI BELAJAR SISWA - man, Herman man (Makassar Journal of Social Sciences, 2013)
This study aims to describe the level of participation of parents Junior High School I Kajuara in Bone and to describe the level of achievement of social studies students SMP I Kajuara in Bone and determine the influence of parental involvement on student achievement Junior High School I Kajuara Bone County.This study uses a quantitative study with a population of 57 , because the population is relatively large and can not be researched all that is necessary to determine a sample of the population of the 36 people which is 16 % of the population for this study is a research sample. Data collection was done by using the questioner, observation, interviews and documentation . The data analysis technique used is descriptive statistical analysis and inferential statistical analysis .The results showed that: The level of parent participation are in both categories, with the average value ( mean ) of the participation of parents ( variable X ) at 72.06 where the average value is consulted in Table 6 are at intervals of 63-77 with a frequency of 29 students which means belonging to the category of " good ", with a standard deviation of 5.440. Achievement social studies students of SMP Negeri I Kajuara Bone district classified in the category of " good ' ', seen from the average value ( the mean ) for student learning outcomes ( Y ) at 81.61 which is in the range 75-89 with a standard frequency deviation of 3.417 with 34 students from 36 students. The results of hypothesis testing showed that there was a significant relationship between the participation of parents of students in social studies achievement Junior High School I Kajuara Bone County . Where r calculate > r table with sample ( N ) amounted to 36 people or 0.731 > 0.329